AMBIENT AMMONIA STRESS ON CERTAIN METABOLIC ASPECTS IN LIVER TISSUE OF FISH, CYPRINUS CARPIO - P. HARI; P. NEERAJA (The Bioscan, 2011)
Ammonia has received increasing attention over the past few years as potentially important pollutant in aquatic system mainly due to the indiscriminate use of fertilizers and pesticides. Ammonia is toxic to living animals and produces several biochemical and physiological changes at cellular level when present in higher concentration. In view of these some of the important physiological and biochemical events occurring under ammonia in the fish animal were taken for the study. Fish Cyprinus carpio is taken for the present study. Animal weighting 120±10g and 17±2 cm length are exposed to 4 ppm of ammonia solution for 7days. In order to understand the effect of chronic ammonia stress on the detoxification aspect of the liver tissue, total protein, ammonia, urea content and activity levels of arginase, Glutathione peraxidase (GPx), Glutathione–s-Transferase (GST), Glutamate dehydrogenase (GDH), Superoxide dismutase (SOD) enzyme levels were estimated in the liver tissue of the animal. A decrement in total protein content along with increment in ammonia and urea and increased activity levels in GPx, GST, GDH and SOD enzyme levels was observed on prolonged ammonia exposure.